Transnational migration and the new subjects of work : transmigrants, hybrids and cosmopolitans. - Ozkazanc-Pan, Banu, 1975- (Bristol University Press, 2019)
A first in utilising transnational migration studies as a new theoretical framework in management and organization studies, this book presents a much-needed new concept for understanding people, work and organizations in a world 'on the move' while attending to growing inequality associated with work in changing societies.